2016
DOI: 10.7554/elife.20522
|View full text |Cite
|
Sign up to set email alerts
|

A complete toolset for the study of Ustilago bromivora and Brachypodium sp. as a fungal-temperate grass pathosystem

Abstract: Due to their economic relevance, the study of plant pathogen interactions is of importance. However, elucidating these interactions and their underlying molecular mechanisms remains challenging since both host and pathogen need to be fully genetically accessible organisms. Here we present milestones in the establishment of a new biotrophic model pathosystem: Ustilago bromivora and Brachypodium sp. We provide a complete toolset, including an annotated fungal genome and methods for genetic manipulation of the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(106 citation statements)
references
References 124 publications
1
99
0
Order By: Relevance
“…Moreover, the current setup is of high practical use for work in the U. bromivora – B . distachyon model system (Rabe et al ., ), because it may drastically shorten the time to evaluate infection outcome, for example in fungal virulence factor or host R‐gene mutants, and allow for the targeted study of the infection stages before qualitative symptom establishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the current setup is of high practical use for work in the U. bromivora – B . distachyon model system (Rabe et al ., ), because it may drastically shorten the time to evaluate infection outcome, for example in fungal virulence factor or host R‐gene mutants, and allow for the targeted study of the infection stages before qualitative symptom establishment.…”
Section: Discussionmentioning
confidence: 99%
“…21°C with the fungal solution for 12–24 h. Seedlings were subsequently planted and vernalized as described by Rabe et al . (). Plants flowered c .…”
Section: Methodsmentioning
confidence: 99%
“…In smut fungi, effectors are often found in clusters as a result of gene duplication events followed by this accelerated evolution. This has led to a relatively low degree of conservation among smut effectors in general (Kämper et al, ; Laurie et al, ; Rabe et al, ; Schirawski et al, ). In this respect, Cce1 is an atypical smut effector as it is not clustered with other putative effector genes and does not have any paralogs.…”
Section: Discussionmentioning
confidence: 99%
“…Complete genomes of five species of closely-related genera and varying in mating-type organization are available: tetrapolar U. maydis (116) and Sporisorium reilianum (117), and the bipolar species U. hordei , with the HD and P/R loci 430 – 500 kb apart (118), Sporisorium scitamineum , with the HD and P/R loci 59 kb apart (119, 120) (Fig. 3B) and Ustilago bromivora , with the HD and P/R loci 183 kb apart (121). By comparing chromosomal rearrangements between U. maydis, U. hordei and S. reilianum , it was suggested that the tetrapolar organization in the S. reilianum lineage was ancestral, and that part of S. reilianum chromosome 1 harboring the HD locus was translocated to its chromosome 20 harboring the P/R locus, to generate the bipolar organization in U. hordei (118).…”
Section: Breeding Systems In the Basidiomycotamentioning
confidence: 99%